2022
DOI: 10.1111/clr.14005
|View full text |Cite
|
Sign up to set email alerts
|

Two‐piece zirconia implants in the posterior mandible and maxilla: A cohort study with a follow‐up period of 9 years

Abstract: Objectives: Long-term follow-up observations of zirconia implants are rare. This study aimed at evaluating the clinical performance of two-piece zirconia implants in the posterior jaws over 9 years. Materials and Methods:Sixty partially edentulous patients were treated with twopiece zirconia implants. In eight no primary stability could be achieved. Fifty-two patients received the final restoration (i.e., cemented fibreglass abutments and allceramic crowns). After 2 years, 2 implants failed and 4 dropouts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 66 publications
(98 reference statements)
0
18
0
Order By: Relevance
“…After appropriate treatment, these infections could be successfully treated and no further cases of peri‐implantitis could be observed until the last follow‐up. However, at the 9‐year follow‐up, signs of inflammation (bleeding on probing) were observed around 13 implants (Brunello et al, 2022). In another study, peri‐implantitis was diagnosed around 1 out of 71 initially placed 1‐piece zirconia implants after 5 years of investigation, whereas the implant was included in a cumulative therapy, starting with non‐surgical procedures (Balmer et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After appropriate treatment, these infections could be successfully treated and no further cases of peri‐implantitis could be observed until the last follow‐up. However, at the 9‐year follow‐up, signs of inflammation (bleeding on probing) were observed around 13 implants (Brunello et al, 2022). In another study, peri‐implantitis was diagnosed around 1 out of 71 initially placed 1‐piece zirconia implants after 5 years of investigation, whereas the implant was included in a cumulative therapy, starting with non‐surgical procedures (Balmer et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…After implant placement and unloaded healing of 10–12 weeks, fiberglass abutments as well as single crowns were cemented. After a mean follow‐up period of 111.1 months (±2.2), 32 implants were evaluated, and the authors reported a survival rate of 93.8% (Brunello et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations